Penerapan Pencatatan Keuangan Digital pada UMKM dalam Mewujudkan SDGs Desa - Happy Nur Virdiana; Dewi Deniaty Sholihah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Micro, Small and Medium Enterprises (MSMEs) in villages have a central role in achieving Sustainable Development Goals (SDGs). The main factor in achieving sustainable development goals at the village level is efficient financial recording at the MSME level. However, MSMEs do not fully understand managing financial records. As a result, MSMEs are unable to handle financial records and evaluate business performance consistently and correctly. To overcome this problem, outreach and training activities have been carried out in Gunung Anyar Tambak RW 08 Village using the Buku Warung financial application for MSMEs. The aim of this activity is to increase the use of technology and provide a better understanding of how to minimize errors, strengthen financial report recording, and at the same time support the achievement of local SDGs. This activity succeeded in increasing MSMEs' awareness of financial recording through outreach which included methods of presenting material, direct practice, monitoring and evaluation. As a result, they can make the financial recording process more structured and efficient by using the Buku Warung application on their smartphone. In conclusion, the application of the Buku Warung financial application provides in-depth insight into how technology can play a key role and provide a positive impact in advancing sustainable development at the village level.